The Persian Whitman: Beyond a Literary Reception - Mostafa Hosseini (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
The Persian Whitman is comprised of an introduction, nine chapters, a conclusion and an appendix. The book is an interdisciplinary study. On the one hand, it deals with Comparative Literature (reception studies and imagology) and Literary Criticism (New Historicism), on the other hand, it deals with Translation Studies (translation and ideology and Genette’s paratextual elements). The Persian Whitman is about Whitman’s reception in Iran in a period of 100 year. To sum up, The Persian Whitman is a methodologically innovative, original, and well-documented interdisciplinary study. The author’s ideas, interpretations, and conclusions are logical and convincing. More importantly, it is full of innovative readings of familiar and often ignored materials. Putting some unnecessary repetitions aside, The Persian Whitman is a well-organized book which one enjoys reading and learning from. It is highly recommended to those interested in Iranian studies, Comparative Literature, Translation Studies, American literature, and Modern Persian Literature. Key words Comparative Literature, Comparative Literature, Persian Whitman, Reception studies, interdisciplinary study